A study on the benefits of ISO 9001 : 2000 implementation in Malaysia quantity surveying firms - 207308 Chow, Wai Min; Ahmad Rosdan Razak, supervisor; Fakulti Alam Bina (2008)
Project Paper (Sarjana Muda (Ukur Bahan)) - Universiti Teknologi Malaysia, 2008